Development of Islamic Religious Education Teacher Performance for Students in Facing the World of Work - Shofwan, Arif Muzayin; Insani Setyowati, Rina; Hidayah, Choirul (Universitas Nahdlatul Ulama Blitar, 2024)
An Islamic religious education teacher is required to develop his performance so that students are always ready to face the world of work. This qualitative descriptive research using literature study will examine the development of the performance of Islamic religious education teachers for students in facing the world of work. The data analysis technique uses content analysis by sorting data according to the problem and research objectives. This article finds several things as follows. First, in developing their performance, an Islamic religious education teacher must have the following five criteria, including: commitment to students in the learning process, must master the material, carry out evaluations, be able to think systematically, and be part of society in their professional environment. Second, in developing his performance, an Islamic religious education teacher must be able to be a corrector, inspirer, informer, motivator, initiator and facilitator. Also, an Islamic religious education teacher must master several teaching methods, including: lecture methods, exercises, question and answer, discussions, experiments, assignments, field trips, socio-drama, and the like. Third, to prepare students for the world of work, an Islamic religious education teacher must formulate a curriculum that suits the needs of society, that is in line with developments in science and technology, and that suits individual needs. Fourth, to balance the curriculum with the field of work, an Islamic religious education teacher must pay attention to skills education which is usually directed at employment preparation, directed at several types of work and in accordance with his field of expertise.